What is anxious depression? Overlap and agreement between different definitions. (February 2019) - Zimmerman, Mark; Kerr, Sophie; Kiefer, Reina; Balling, Caroline; Dalrymple, Kristy
Abstract: Anxiety is common in depressed patients. However, a problem with the research on the significance of anxiety in depressed patients is that anxiety has been characterized in different ways. Little research has examined the concordance and overlap between the various definitions of anxious depression. With research on the DSM-5 anxious distress specifier just beginning, it will be important to understand how defining anxious depression according to DSM-5 agrees with previously studied definitions. In the present report from the Rhode Island Methods to Improve Diagnostic Assessment and Services (MIDAS) project we examined the association between the DSM-5 anxious distress specifier and 6 other approaches towards defining anxious depression. Three hundred thirty-one patients with a principal diagnosis of major depressive disorder were evaluated with semi-structured diagnostic interviews. The mean number of anxious depression definitions met was 4.7 (SD = 2.1). Only 4.2% (n = 14) of the 331 patients did not meet any anxious depression definition, and 28.1% (n = 93) met all 7 definitions. The level of agreement between the definitions was significant, albeit modest (median kappa = .28). The modest association between the different definitions of anxious depression suggests that the results based on one approach towards subtyping may not generalize to the DSM-5 anxious distress specifier. It therefore cannot be assumed that the DSM-5 anxious distress specifier is valid just because other definitions of anxious depression have been shown to be valid.